Factor affecting the implementation of responsibility accounting on firm performance – Empirical analysis of listed textile firms - Van Tung Tran; Phat Cuong Ly; Ngoc Nguyen Thao Ngo; Phuong Hai Tran; Van Chien Nguyen (Cogent Business & Management, 2022)
There are many researches on different aspects of responsibility accounting system, but none of those researches has focused on the impact of responsibility accounting system on the performance of textile enterprises. The aim of this paper is to identify factors affecting the implementation of responsibility accounting and its effect on the performance of Vietnamese listed textile companies. Using the qualitative and quantitative methodology, qualitative method was used to prepare the questionnaire, while quantitative method was used to measure the scale and analyze the level of impact of each factor. Further, the study employs the Structural equation modeling (SEM) with AMOS-SPSS, results show that factors in the research model aside from measurement technology and level of competition had certain impacts, including the ability of accounting staffs (TDKT), the awareness of managers at different level (NTQL), the decentralization (PQQL), the reward systems (HTKT), and the forecast for responsibility centers (DTTT). In addition, the structural management (CCTC), the competitive strategy (CLCT), the competitive advantages (YTCT) and the responsibility centers' reports (BCTT) that have greatly affected performance of listed firms. In addition, the implementation of responsibility accounting has the greatest effect on the performance of listed companies. In fact, the implementation of responsibility accounting changes by 1 point (level), it will increase/decrease the performance of listed companies by 0.409 points without considering the other factors.
Keywords: 650; listed companies; performance; questionnaire; Responsibility accounting; SEM